Navigating Change in Global Education Systems with Innovative Leadership Approaches - Siswanto; Radiana, Usman (Jurnal Manajemen Pendidikan, 2024)
Background Changes in education in the digital era demand leadership that not only adapts to technology but also provides creative solutions responsive to both local and global needs. Purpose This study aims to explore how innovative leadership approaches can help navigate changes in global education systems, with a focus on West Kalimantan. Design/method/approach This research employs a qualitative approach, with data collection through in-depth interviews, observations, and document analysis in various schools in West Kalimantan. Results The findings indicate that educational leaders who apply innovative approaches, such as integrating technology and enhancing collaboration between teachers and students, are better equipped to overcome the challenges of rapid educational system changes. Moreover, approaches that emphasize collaborative problem-solving contribute to improving teaching and learning quality in schools. In conclusion, innovative leadership plays a crucial role in supporting the transformation of educational systems amidst global change, particularly in regions facing geographical and technological challenges like West Kalimantan. Contribution/value These findings underscore the importance of educational policies that promote innovation and leadership adaptation to meet future challenges.